An Efficient Method for Color-Based Image Retrieval System - Selvam, S.; Thabasukannan, S. (Asian Journal of Electrical Sciences, 2014)
Content-based image retrieval systems retrieve images from a database that are determined to be similar to a query image based only on features extracted from the images. This paper focuses on color-based image retrieval. We define methods to improve the efficiency and effectiveness of color-based retrieval. We have tested our system using a collection of color images and query images. Color histograms are used to extract and store the color content of the images. Our empirical results are very encouraging. The main aim of this paper is to reduce substantially the total color space without degrading retrieval performance. In addition, we are able to improve performance by conducting object retrieval based solely on color.